Formative research on the feasibility of hygiene interventions for influenza control in UK primary schools - Curtis Val; Biran Adam; Wloch Catherine; Schmidt Wolf-Peter; Mangtani Punam (BMC, 2009)
Abstract Background Interventions to increase hand washing in schools have been advocated as a means to reduce the transmission of pandemic influenza and other infections. However, the feasibility and acceptability of effective school-based hygiene interventions is not clear. Methods A pilot study in four primary schools in East London was conducted to establish the current need for enhanced hand hygiene interventions, identify barriers to their implementation and to test their acceptability and feasibility. The pilot study included key informant interviews with teachers and school nurses, interviews, group discussions and essay questions with the children, and testing of organised classroom hand hygiene activities. Results In all schools, basic issues of personal hygiene were taught especially in the younger age groups. However, we identified many barriers to implementing intensive hygiene interventions, in particular time constraints and competing health issues. Teachers' motivation to teach hygiene and enforce hygienic behaviour was primarily educational rather than immediate infection control. Children of all age groups had good knowledge of hygiene practices and germ transmission. Conclusion The pilot study showed that intensive hand hygiene interventions are feasible and acceptable but only temporarily during a period of a particular health threat such as an influenza pandemic, and only if rinse-free hand sanitisers are used. However, in many settings there may be logistical issues in providing all schools with an adequate supply. In the absence of evidence on effectiveness, the scope for enhanced hygiene interventions in schools in high income countries aiming at infection control appears to be limited in the absence of a severe public health threat.